The greenhouse effect - Harris, Jack C. (New York : Crestwood House ; Toronto : Collier Macmillan Canada ; New York : Maxwell Macmillan International, 1990)
Discusses the causes of the greenhouse effect, what it does to our planet, and how it can be stopped.
Includes bibliographical references (p. 44) and index.
Keywords: Greenhouse effect, Atmospheric -- Juvenile literature; Greenhouse effect, Atmospheric; Global warming